Efficacy of Portable Ultrasonography for Early Detection of Pneumothorax Following Lung Biopsy - Won Gun Kwack; Manbong Heo; Yeonseok Choi; Cheon Woong Choi; Byoung Soo Kwon; Yeon Wook Kim; Jong Sun Park; Young-Jae Cho; Jae Ho Lee; Sung Yoon Lim (Tuberculosis and Respiratory Diseases, 2025)
Background Pneumothorax is a notable complication of lung biopsy, and its early detection is crucial. This study aimed to compare the sensitivities of handheld portable lung ultrasonography and chest radiography in identifying early pneumothorax post-lung biopsy. Methods Upright chest radiography and lung ultrasonography were conducted at 3 and 24 hours following lung biopsy. The disappearance of lung sliding and the appearance of lung points on lung ultrasonography were indicative of pneumothorax. Results In this study of 86 patients, 23 were diagnosed with pneumothorax within 24 hours post-biopsy. No significant differences in sex, age, or baseline lung function were noted between the pneumothorax and non-pneumothorax groups. The sensitivities of lung ultrasonography and chest radiography for detecting pneumothorax were 73.9% and 47.8%, respectively, at 3 hours and 91.3% and 78.3%, respectively, at 24 hours. Additionally, at 3 hours, the area under the curve for lung ultrasonography in diagnosing pneumothorax was significantly higher than that for chest radiography (0.870 vs. 0.739, p=0.043); however, the difference was not significant at 24 hours (p=0.254). Conclusion These preliminary findings indicate that lung ultrasonography is more sensitive than chest radiography in detecting early pneumothorax following lung biopsy and could be beneficial for rapid pneumothorax diagnosis.